2021
DOI: 10.1515/cclm-2021-1115
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate concentration in COVID-19: a systematic literature review

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious respiratory condition sustained by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which manifests prevalently as mild to moderate respiratory tract infection. Nevertheless, in a number of cases the clinical course may deteriorate, with onset of end organ injury, systemic dysfunction, thrombosis and ischemia. Given the clinical picture, baseline assessment and serial monitoring of blood lactate concentration may be conceivably useful in COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
5
23
0
Order By: Relevance
“…Of note, in a study of 70 consecutive patients, Yang and collaborators reported that patients with severe disease did not have higher blood lactate values than peers with non-severe illness ( 30 ). Nonetheless, consistent with our results, most studies have demonstrated increased lactate levels in severe and non-survivor COVID-19 patients compared with patients with mild disease ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Of note, in a study of 70 consecutive patients, Yang and collaborators reported that patients with severe disease did not have higher blood lactate values than peers with non-severe illness ( 30 ). Nonetheless, consistent with our results, most studies have demonstrated increased lactate levels in severe and non-survivor COVID-19 patients compared with patients with mild disease ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…[ 41 , 42 ]. Severe COVID-19 is associated with elevation of blood lactate and acidosis [ 43 , 44 ], which enables Candida to restructure its cell wall to mask β-glucans and escape the recognition by the host immune system [ 45 ]. Moreover, an important virulence factor of Candida that helps it evade phagocytosis is the ability to form biofilms, which can be triggered by COVID-19 through increasing oxidative stress and pH imbalance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies found that LDH is a useful biomarker for acute mesenteric ischemia, [ 55 , 56 ]. However, interpretation of the results may be difficult in COVID-19 patients, as both lactate and LDH were also found to be independent risk factors of severe forms of COVID-19 [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%